2021
DOI: 10.1021/acsanm.1c02315
|View full text |Cite
|
Sign up to set email alerts
|

Flower-Like Molybdenum Disulfide Nanostructures for Promoting Mitochondrial Homeostasis and Attenuating Inflammatory Endothelial Dysfunction

Abstract: Mitochondrial dynamics is crucial to cellular metabolic homeostasis, development, and remodeling. However, the perturbation of mitochondrial dynamics impairs endothelial functions, leading to numerous diseases, including cardiovascular diseases. The few-layered molybdenum disulfide (MoS 2 )-based nanoagents hold great potential as therapeutic agents for various disorders. Herein, we investigated whether flower-like MoS 2 nanosheets (FL-MoS 2 ) promote mitochondrial homeostasis via modulating mitochondrial dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Abundant studies have demonstrated the anti-inflammatory action of MoS 2 nanoparticles on different cells [ 39 , 40 ], and the results of that study support our findings. The mechanisms of action by which the DSPE-PEG-TPP/MoS 2 QD blend was able to produce neuroprotective effects and reduce inflammation were not mentioned; however, many studies using natural products and pharmacological drugs have reported that a protective effect against Aβ oligomers-induced microglial activation and inflammation cascades is achieved via suppression of the master switch for microglial activation, i.e., the transcription factor nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), which plays a crucial regulatory function in the generation of inflammatory mediators resulting in neurotoxicity.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Abundant studies have demonstrated the anti-inflammatory action of MoS 2 nanoparticles on different cells [ 39 , 40 ], and the results of that study support our findings. The mechanisms of action by which the DSPE-PEG-TPP/MoS 2 QD blend was able to produce neuroprotective effects and reduce inflammation were not mentioned; however, many studies using natural products and pharmacological drugs have reported that a protective effect against Aβ oligomers-induced microglial activation and inflammation cascades is achieved via suppression of the master switch for microglial activation, i.e., the transcription factor nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), which plays a crucial regulatory function in the generation of inflammatory mediators resulting in neurotoxicity.…”
Section: Resultssupporting
confidence: 90%
“…One previous study found that flower-like MoS2 nanosheets (FL-MoS2) caused endothelial cells to shift toward mitochondrial fusion rather than fission, as demonstrated by increased expression of mitochondrial fusion proteins (Mfn2, Opa1) and decreased expression of fission proteins (Fis1) which promote mitochondrial homeostasis [39]. Lastly, the anti-inflammatory impact of the DSPE-PEG-TPP/MoS2 QD blend on microglial cells activated by Aβ was determined using the ELISA technique and real-time PCR analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations